Innovation in Freshwater Fish Processing for Value Addition to Enhance Income and Food Security in Lamongan - Siti Musarofah; Tri Winarsih; Ma'rufatur Rodiyah; Panji Winoto; Anggraeni Sovi Maria Septiana (Society : Jurnal Pengabdian Masyarakat, 2026)
This community service program was carried out in Banjarejo Village, Kedungpring Subdistrict, Lamongan Regency, with the aim of increasing the added value of freshwater fish through product innovation. The village’s fishery potential, which has so far only been marketed in the form of fresh fish, has resulted in low selling prices and limited community income. To address this problem, the service team applied the Participatory Action Research (PAR) method by involving 20 village youths. The activities included socialization, training in the production of processed fish products (smoked fish, nuggets, and presto fish), training in packaging design, digital marketing, and business mentoring. The results of the program showed that participants were able to produce and package processed fish products properly. The evaluation indicated that 85% of participants could independently repeat the processing techniques. The tangible impact of this activity was an increase in the selling price of fish from IDR 15,000–18,000/kg to IDR 40,000–60,000/kg. In addition to providing economic benefits, this program also supports local food security by providing nutritious products based on freshwater